Effects of lumbosacral and lumbopelvic fixation and fusion on hip joint motor function: a single-center prospective cohort study using gait analysis - Zhang, Fansheng; Bian, Shuyuan; Gaxi, Shijia; Tian, Xiaobin; Li, Bo; Guo, Tao (Frontiers in Surgery, 2026)
ObjectiveTo evaluate the effects of lumbosacral and lumbopelvic fixation and fusion on hip motor function using a three-dimensional gait analysis system.MethodsThis single-center prospective cohort study enrolled adult patients who underwent lumbosacral or lumbopelvic fixation and fusion in the Orthopedics Department of Guizhou Provincial People's Hospital between November 2015 and January 2020. The patients were followed up postoperatively for over 1 year. During follow-up, the pain levels, functional impairment, and clinical outcomes of the patients were assessed using the Visual Analogue Scale score, Oswestry Disability Index, and Japanese Orthopedic Association score. Hip motor function was evaluated through a three-dimensional measurement system that assessed the hip, knee, and ankle joints. Data analysis was conducted using SPSS V22.0. This study was designed and reported to adhere to strengthening the reporting of observational studies in epidemiology (STROBE) guidelines for observational research.ResultsA total of 30 patients were included in the study, with 15 undergoing lumbosacral prosthesis and 15 who underwent lumbopelvic fixation. The mean follow-up period was 13.8 months. A kinematic analysis revealed that, compared with healthy controls, patients who underwent lumbosacral fusion showed decreased minimum step length, maximum stride length, maximum angle, and range, while up-down and up-front displacements increased significantly (p < 0.05). Similar outcomes were observed in patients after lumbopelvic fixation and fusion, with an increase in maximum stride length compared with healthy controls (p < 0.05). When directly comparing the two groups, it was found that those who underwent lumbosacral fusion demonstrated greater maximum stride length, maximum hip flexion angle, and range of hip flexion and extension than those who underwent lumbopelvic fixation (p < 0.05).ConclusionBoth lumbosacral and lumbopelvic fixation and fusion significantly impact hip joint motor function compared with healthy controls. However, the increased mobility of the femoral head relative to the acetabulum in these patients may elevate the risk of hip osteoarthritis and cartilage wear. Within the scope of parameters measured in this gait analysis, patients receiving lumbosacral fixation demonstrated superiority in specific gait parameters, including maximum stride length and hip flexion–extension range of motion, compared with those who underwent lumbopelvic fixation. This suggests that preserving sacroiliac joint mobility may be beneficial for certain aspects of walking function when clinically justified.